Assessment of Natural Resource Potential of the Landscape of Mongolia (Based on Agricultural Production Resource) - Munkhtur, Purevsuren; Erdenedalai, Avirmed (Proceedings of the Mongolian Academy of Sciences, 2020)
The landscape contains a variety of different potentials that can perform socio-economic and ecological functions, since landscapes are surface patterns that differ in appearance, environmental components, and their spatial distribution and location. The natural resource potential of the landscape refers to the ability of a landscape to provide society with the raw materials and natural resources, which are required for manufacturing products in the society. The natural resource potential of the landscape can be estimated based on mineral resources, forest resources, agricultural production resources, hunting, and tourism or recreation resources. The purpose of this research was to evaluate the natural resource potential of the landscape based on agricultural production resources. This research was carried out with combined methodology, which involved market price method that was used for assessing agricultural production resources with a GIS-based analytical hierarchy process that was used for developing the potential assessment. The analysis of the spatial distribution map of the natural resource potential of the landscape showed that 41.0 per cent of the area studied had “average” potential, while 34.8 per cent had “low” potential and 19.4 per cent had “high” potential. However, only 2.3 per cent of the area had “very high” potential in terms of potential assessment, whereas, almost the same amount of area (2.5%) was assessed as with “very low” potential. Evaluating the natural resource potential of the landscape, based on agricultural production resources, is important as fundamental information for further research, such as developing a concept of regional economic development and evaluating ecosystem services.